Diabetes Mellitus Detection Expert System Using a WEB-Based Naïve Bayesian Approach - Suardin Yakup (Institute of Computer Science (IOCS), 2020)
Health is the most important factor in a person's life. If health has been disturbed (sick) then a person's activities will be disrupted. Today, many diseases have a large number of sufferers and are even effective killing machines. One of them is diabetes mellitus, which is a disease with the highest number of patients, which is as many as 230 people. In Indonesia alone, the number of diabetic patients reached 4.5 million people in 1995 and it is estimated that by 2025 there will be 12.4 million people with diabetes and ranks fifth in the world. This increasing number every year is not supported by an increase in the number of specialist doctors who can treat this disease, so that many sufferers are not diagnosed with diabetes. Advances in the world of technology really help the modern world to detect or predict something that will happen. One of them is an expert system used to detect a disease in medicine. The relationship between expert systems and Islam is explained in many ways in the Qur'an, especially in Surah Al-Hasyr verse 18. The word Nadhar means reason or thought. Reasoning activities are related to the brain or reason. In the context of science, nadhar can be interpreted as an expert system. Because both of them have the benefit of knowing things that will happen or for predicting and even detecting things that will happen. Intellect can determine the goodness or badness of something that is non-physical, while the expert system is used to detect or determine the presence or absence of diabetes mellitus in a person.